Safety and efficacy of stand-alone anterior lumbar interbody fusion in low-grade L5-S1 isthmic spondylolisthesis - C. Marvin Jesse; Othmar Schwarzenbach; Christian T. Ulrich; Levin Häni; Andreas Raabe; Ralph T. Schär (Brain and Spine, 2022)
Introduction: Surgical management of isthmic spondylolisthesis is controversial and reports on anterior approaches in the literature are scarce. Research question: To evaluate the safety and efficacy of stand-alone anterior lumbar interbody fusion (ALIF) in patients with symptomatic low-grade L5-S1 isthmic spondylolisthesis. Material and methods: All adult patients with isthmic spondylolisthesis of the lumbosacral junction treated in a single institution between 2008 and 2019 with stand-alone ALIF were screened. A titan cage was inserted at L5-S1 with vertebral anchoring screws. Prospectively collected surgical, clinical and radiographic data were analyzed retrospectively. Results: 34 patients (19 men, 15 women, mean age 52.5 ​± ​11.5 years) with a mean follow-up of 3.2 (±2.5) years were analyzed. 91.2% (n ​= ​31) of patients had a low-grade spondylolisthesis and 8.8% (n ​= ​3) grade III according to Meyerding classification. Mean COMI and ODI scores improved significantly from 6.9 (±1.5) and 35.5 (±13.0) to 2.0 (±2.5) and 10.2 (±13.0), respectively after one year, and to 1.7 (±2.5) and 8.2 (±9.6), respectively, after two years. The COMI and ODI scores improved in 86.4% and 80%, respectively, after one year and 92.9% of patients after two years by at least the minimal clinically important difference. No intraoperative complications were recorded. 8.8% (n ​= ​3) of patients needed a reoperation. Discussion and conclusion: After stand-alone ALIF for symptomatic isthmic spondylolisthesis, the patients improved clinically important after one and two years. Stand-alone ALIF is a safe and effective surgical treatment option for low-grade isthmic spondylolisthesis.